Convective-Radiation Drying of Foamed Gelatin Fish Broth - Makarov A.; Maksimenko Y.; Dyachenko E. (Техника и технология пищевых производств)
Introduction. The mechanical characteristics of foam gelatin broth make it a promising material for studying the process of obtaining dry gelatin. The preliminary foaming of the product and the use of infrared (radiation) energy supply during its dehydration can significantly improve the process. Study objects and methods. The research featured gelatinized gelatin broth prepared from fish wastes. The efficiency of the proposed drying method was assessed by comparative studies of the kinetics and intensity of convective and convective-radiation foam drying. Specific productivity of the process was selected as evaluation criterion. Results and discussion. The paper introduces a method of convective radiation foam drying of gelatinized fish broth. A set of experiments made it possible to define the optimal process conditions with the maximum yield of dry gelatin, i.e. 0.998 kg/(m2·h): initial concentration of solids in the product C = 0.24 kg/kg; temperature T = 292–295 K, humidity W = 50–60%; the speed of the drying agent v = 4–5 m/s; the initial diameter of the foam rod dI = 0,004 m; the density of the heat flux incident on one side of the rod E = 2.45 kW/m2; the wavelength of infrared emitters λ = 1.01–1.11 microns. The research revealed the effect of the main factors influencing the drying process on the approximating dependences of the specific yield of dry gelatin from a unit area of the working surface per unit of time. The introduction of radiation energy supply into the process of convective foam drying of gelatinized broth under rational conditions was three times as high as the specific productivity of the process. An analysis of the kinetics of convective and convective-radiation drying helped to obtain some functional dependences of the drying speed of the foamed gelatin broth extrusions from the concentration of dry substances in the product for the considered process conditions. An analysis of heat and mass transfer during convective-radiation foam drying was performed using the velocity curves. The nature of the change in the drying rate of the product proved typical of most biopolymers. Conclusion. The results obtained are applicable in the calculations of the productivity of drying equipment in dry gelatin production and other products with similar complex properties.